PENGARUH EDUKASI 1000 HARI PERTAMA KEHIDUPAN SEBAGAI UPAYA PENCEGAHAN STUNTING TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL - Tyani, Indrawati Aris; Setyawati, Ari; Resmi, Dewi Candra; Khoiriyah, Siti; Indriani, Farihah; Romdiyah, Romdiyah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
Pupose of the research was to determine the effect of education in the first 1000 days of life as an effort prevent stunting on the knowledge and attitudes of pregnant women. Method used a one group pre-test and post-test design, the research sample using a purposive sampling technique obtained a total of 34 respondents. Respondents were asked to fill out a questionnaire before and after being given education in the first 1000 days of life as an effort prevent stunting regarding the knowledge and attitudes of pregnant women. Data were subjected to univariate and bivariate tests to be analyzed using the Wilcoxon test to determine the effect of education in the first 1000 days of life on the knowledge and attitudes of pregnant women in preventing stunting. Results of the research show that the pretest of respondents showed that 16 (47.06%) respondents had less knowledge and 23 (67.65%) respondents had negative behavior. Meanwhile, in the posttest, the majority of respondents had good knowledge, 22 (64.71%) and 27 (79.41%) respondents with positive behavior. After providing education for the first 1000 days of life as an effort prevent stunting to pregnant women, the p-value for pretest and posttest maternal knowledge was 0.000 and pretest and posttest maternal behavior was 0.000. Conclusion is is that there is an influence of education in the first 1000 days of life as an effort prevent stunting on the knowledge and attitudes of pregnant women.